APITAN AND THE SOCIO-ECONOMIC DYNAMICS OF GROBOGAN SOCIETY (20TH CENTURY) - ABDUL AZIZ; DEVI INDRIYANI (JUSAN: Jurnal Sejarah Peradaban Islam Indonesia, 2023)
Apitan, a longstanding tradition in Grobogan, Central Java, holds its roots in the Hindu-Buddhist era. This cultural practice has significantly shaped and transformed the socio-economic and religious landscape of the community, making it imperative to investigate how Apitan has influenced the social, economic, and religious dynamics of Grobogan in the 20th century. This research employs a historical approach with a social perspective. The findings of this study reveal that Apitan bestows numerous benefits upon the Grobogan community. Notably, it fosters camaraderie not only among fellow Muslims but also between individuals of different faiths. Furthermore, this tradition serves as a means of disseminating historical insights, perpetuated through community rituals. From a socio-economic standpoint, it has evolved over time, primarily functioning as a platform for the promotion and introduction of halal food and a halal lifestyle. In the pre-independence era, marked by challenging circumstances and limited education, the accessibility of non-halal food forced the populace to consume it. Although Apitan continues to be celebrated annually, local traditions face significant challenges in the modern global era. The younger generation is progressively less engaged and interested in the Apitan tradition. This predicament necessitates a multi-faceted approach, addressing both the challenges of the times and finding solutions to preserve the local Muslim community's traditions.